A new therapeutic strategy for gastroesophageal reflux disease resistant to conservative therapy and monotherapy in preterm neonates: a clinical trial - Negar Sajjadian; Zahra Akhavan; Peymaneh Alizadeh Taheri; Mamak Shariat (Hygeia Press di Corridori Marinella, 2019)
Background: Gastroesophageal reflux disease (GERD) is one of the most common problems in neonates. The main clinical manifestations of GERD are frequent regurgitation or vomiting associated with irritability, anorexia or feeding refusal, failure to thrive, Sandifer posturing, apnea, bradycardia and stridor in infants. Since the clinical manifestations of GERD are often non-specific in preterm infants, it has been described as the clinical syndrome responding to anti-reflux treatment. Aims: To our knowledge, no clinical trial has compared the efficacy of histamine-2 receptor antagonists (H2RAs) and proton pump inhibitors (PPIs) in preterm infants, nor has any study assessed the effect of adding a prokinetic agent to an acid suppressant and compared them together in these infants, so the present study was conducted. Study design: This study was performed on 58 preterm newborns (mean age, 9.72 ± 6.78 days, 43.2% boys and birth weight of 1,571.9 ± 596.59 grams) with GERD resistant to conservative therapy and monotherapy hospitalized in neonatal wards and NICUs of Shariati and Bahrami Children Hospitals during 2014-2016. Neonates were randomly assigned to a double-blind trial with either oral metoclopramide plus omeprazole (group A) or oral metoclopramide plus ranitidine (group B). After one week and one month, their symptoms and signs were evaluated again. The response rate in each group was the primary outcome and the side effect of drugs in each group was the secondary outcome. Results: Our study showed that both regimens were effective in the treatment of GERD resistant to conservative therapy and monotherapy in premature infants. The response rate of "omeprazole plus metoclopramide" was significantly higher than the response rate of "ranitidine plus metoclopramide" (91.37 ± 7.5 vs. 77.06 ± 3.38, respectively; p = 0.04) (primary outcome). There were no drug-related complications of drugs in both groups in our study (secondary outcome). Conclusion: This study showed that combined therapy led to the response rate of > 70% in each group, but it was significantly higher in group A (> 90%). Both combination therapies led to higher response rate in comparison with conservative therapy and monotherapy used before intervention.